Distance without Remoteness: The Objectivist Poetics of Nonmimetic Pain - Xavier Kalck (Transatlantica)
This article begins by briefly examining some of the history of reading in terms of the critical relationship between mind and body, with a view to moving beyond any sense of a simple opposition between the two. Going back (shortly) to the roots of western literacy and now little-known meditative mind-body techniques, it emphasizes the once healing value of reading with an embodied mind. This article then proposes to compare three excerpts––all written after 1945––from the work of three US poets (George Oppen, Charles Reznikoff and Louis Zukofsky) which all deal with the experience and trauma of World War II. In doing so, this article will show how all three attempted to produce accounts of, or to reflect upon, what had taken place in a way that would not allow for any forms of aestheticization and that would show extreme caution when engaging with readers’ sensitivities. This article concludes that, while such poetics may seem far removed from today’s emphasis on reading as a sensory and indeed somatic event, these poets’ practice of mitigating and even of attempting to heal from the suffering that had accumulated still does hold precious insights into what and how literature can or should make us feel.